Fungi Associated with Medicinal Juniper Tree Roots Juniperus Phoenicea L. at Al-Jebal-AL-Akhdar-Libya - Nagah Abubaker; Abeer Ali (AlQalam Journal of Medical and Applied Sciences, 2021)
Objectives. The present study conducted during April 2016 in area at Al-Jebal Al-Akhdar-Libya. The goal of this study was to identify fungal species isolated from roots of Juniperus phoenicea L. Methods. Fungal growth was assessed after seven days of incubation at 28°C. Colony diameter, culture characteristics (texture, surface, reverse coloration, zonation and sporulation of fungi) were observed. Identification and characterization of the fungi were made with the help of authentic manuals of soil fungi and confirmed by the Region Center for Mycology and Biotechnology in Al-Azhar University. Results. The current results reported the presence of 24 fungal species belonged to 14 genera. The isolated fungi were identified as Microphaeropsis olivacea, Trichoderma viride, Rhizopus azygosporus, Alternaria alternata, Fusarium oxysporum, F. poae, F. tabacinum, F.dimerum, Emericella nidulans, Aspergillus niger, A. niveus, A. candidus, A. terreus var. aureus, Penicillium crustaceum, P. simplicissium, P. steckii, P. wortmanniim, Plectosporium tabacinum, Cunninghamella bertholletiae, Trichophytom verrucosum, Memnoniella echinata, Pseudallescheria boydii Talaromyces assiutensis and T. trachyspermus were prevalent in the roots samples. Result shows the highest frequency and occurrence of roots fungi were A. niger 75%. Conclusion. The present study shows that presence of 24 fungal species belonged to 14 genera were isolated from roots of J. phoenicea L. They include 2 Zygomycetes, 7 Ascomycetes, 5 Deuteromycetes. therefore, the highest frequency and occurrence of roots fungi were A. niger 75%.